Room‐Temperature Crystallization of CuS Nanostructures for Photothermal Applications through a Nanoreactor Approach. Issue 20 (31st May 2017) - Morgese, Giulia; Dolcet, Paolo; Feis, Alessandro; Gellini, Cristina; Gialanella, Stefano; Speghini, Adolfo; Badocco, Denis; Pastore, Paolo; Casarin, Maurizio; Gross, Silvia
Abstract : An inverse (water in oil) miniemulsion technique was successfully implemented for the first time for the synthesis of crystalline pure and doped CuS nanostructures for applications in photothermal therapy. Different copper and sulfur sources were tested for the preparation of the targeted compounds. The successful formation at room temperature of the covellite crystalline phase was determined by means of X‐ray diffraction crystallography, selected‐area electron diffraction, and X‐ray absorption spectroscopy. The morphology of the nanostructures was assessed by scanning and transmission electron microscopy, while the surface composition was determined by X‐ray photoelectron spectroscopy. Further investigations, aimed at obtaining a characterization as detailed as possible, were performed by combining the outcomes of complementary techniques. Droplet‐size variations, as a function of sonication time and/or mode, were studied using dynamic light‐scattering measurements. A high microscopic photothermal conversion efficiency – a relevant property for photothermal therapy and photoacoustic imaging – was determined by calibrated optoacoustic measurements. The photothermal efficiency of diluted aqueous dispersions of the CuS nanostructures is ≥ 0.72, as determined by laser excitation at 1064 nm. Abstract : An inverse (water in oil) miniemulsion technique is successfully employed for the first time for the synthesis of crystalline CuS nanostructures, which show high photothermal efficiency.